THE MEDICAL SIGNIFICANCE OF THE COMPLEX COMPOUND OF PECTIN WITH ZINC METAL (The New Uzbekistan Journal of Medicine, 2025)
Fundamental scientific research is being actively conducted in the world today on the synthesis of polymer-metal complexes and the creation of promising drugs for different purposes. In this regard, it is an urgent task to obtain polymer-metal complexes with biological activity, to determine their physico-chemical properties and possible areas of their application. The purpose of the research: to obtain complexes of pectin with some metals and to study their physical and chemical properties.